High temperature is essential for preserved human sperm function during the devitrification process. (3rd February 2015) - Mansilla, M. A.; Merino, O.; Risopatrón, J.; Isachenko, V.; Isachenko, E.; Sánchez, R.
Summary: Sperm vitrification is a cryopreservation method based on high‐speed freezing by direct exposure of cells in liquid nitrogen (N2 L), thereby avoiding the traditional cooling curves of freezing. The objective of this work was to determine the optimal warming temperature for vitrified human spermatozoa in order to maintain their fertilisation potential. Spermatozoa were cryopreserved by direct plunging into N2 L and warmed at different temperatures for 5 and 10 s at 38, 40 and 42 °C. Sperm motility was evaluated by the CASA system and the sperm membrane function by HOST test. It was detected that progressive motility of sperm warmed at 38, 40 and 42 °C was 26.4 ± 8.4%; 56.6 ± 16.3% and 65.4 ± 15%, respectively, with statistically significant differences between the temperatures of 38 and 40 °C and 38 and 42 °C ( P < 0.05). The plasma membrane function evaluated by HOST test was better preserved at 42 °C (76.3 ± 2.0%) compared to 40 °C (43 ± 2%) and 38 °C (65.6 ± 1.5%). The temperature in the thawing process can affect the motility and plasma membrane integrity and function. The warming at 42 °C for thawed vitrified sperm is the optimum temperature to preserve the sperm physiological parameters.